Young Australians : The best of young Australia, exhibited by Budget rent a car (Melbourne : Powell Street Gallery, 1987)
Arkley, Howard ; Barberis, Irene ; Bezor, annette ; Bush, Stephen ; Campbell, Jon ; Cattapan, Jon ; Clark, Tony ; Cox, Stephen ; Dyson, Chris ; Eirth, Merrin ; Ellis, Peter ; Ewert, Christine ; Farley, Stanley ; Fairskye, Merikyn ; Faulks, Philip ; Furlonger, Joe ; Gaha, Adrienne ; etc.
Young Australians : The best of young Australia, exhibited by Budget rent a car. During the next two years, the Exhibition will travel to all capital city galleries and many regional galleries throughout the country.
boek
Keywords: Australië